Моделювання та візуалізація максимальних багатопродуктових потоків у мережі - Додонов, Є.О.; Додонов, О.Г.; Кузьмичов, А.І. (Реєстрація, зберігання і обробка даних, 2018)
Розглянуто багатопродуктові потоки — звичайну природну ситуацію, коли неперервні чи дискретні потоки будь-чого, пасажирів, транспортних засобів, води, електроенергії, сировини, продукції чи інформації, одним словом — продуктів (commodity), рухаються в мережі від одного вузла до іншого. Тут один і той же вузол може бути одночасно джерелом потоків одного чи кількох продуктів (товарів чи послуг), стоками та проміжними пунктами потоків різних продуктів, а кожна дуга — каналом одночасного руху потоків різних продуктів у визначеному напрямку із обмеженою пропускною здатністю. Представлено методику розв’язання задачі мережевої оптимізації про максимальний багатопродуктовий потік у ненаправленій мережі із застосуванням доступних засобів комп’ютерного моделювання. Рассмотрены многопродуктовые потоки, которые являются обычными и естественными понятиями, когда непрерывные или дискретные потоки чего-либо, пассажиров, транспортных средств, воды, электричества, сырья, продуктов или информации, перемещаются в сети из одного узла к другому. Здесь узлы могут одновременно быть источниками, промежуточными пунктами или стоками потоков одного или разных продуктов, а каждая дуга является каналом одновременного пропуска потоков разных продуктов в определенном направлении с ограниченной пропускной способностью. Предложена методика решения задачи о максимальном многопродуктовом по-токе с использованием стандартных инструментов линейной оптимизации. Multiproduct flows are the usual natural situation when continuous or discrete flows of anything, passengers, vehicles, water, electricity, raw materials, products or information, shortly, commodities, are moving in the network from one node to another. Here, the node can simultaneously be the source, intermediate point or terminal of one or different commodities (goods or services) flows of products, and each arc is a channel of simultaneous flow of different products in a definite direction with limited capacity. The multi-product flow problem is an important component of the network optimization, which can be used to deal with problems arising, for example, in emergency logistics management, in computer science and technique, in communication and transportation systems performance, in product distribution planning, in network design etc. This is both an ancient and new line of research. The amount of flow one can push through a network from a source to a sink clearly cannot exceed the capacity of a cut separating them, and max-flow min-cut theorem of Ford and Fulkerson showed that the capacity upper bound is always tight. The value of the maximum flow is equal to the capacity of the minimum cut. A technique for solving the maximum multi-product flow problem with using standard linear optimization tools built-in in Excel is proposed.The developed technique for modeling the problem of the maximum K-commodity flow allows investigating practical network situations reduced to a linear model, having the ability, unlike the heuristic (approximate) algorithms, to automatically determine precisely the separating set as the critical zone, to the definition which often focuses as the subject. This technique does not require additional tools or programming skills, therefore it is a perfect software product for research and development in any field of information and analytical activity.